Android-based patient healthcare tracker with appointment booking capability - Idris, Fakrulradzi; Ramalingam, Suhasshini; Hashim, Norlezah; Ruslan, Eliyana; Johal, Muhammad Syahrir; Darus, Muhamad Firdaus (Semarak Ilmu Publishing, 2024)
Managing the healthcare system presents various challenges that healthcare professionals must be well-prepared to address. Additionally, in times of pandemics, reducing human contact in crowded locations like clinics becomes crucial. Currently, many clinic departments spend a considerable amount of time manually entering and searching for patient data within their systems. This process is not only time-consuming but also notably ineffective. Hence, the development of a mobile application has become an imperative solution to overcome these issues. This project has been implemented using Android Studio with the primary aim of tracking patient health and efficiently recording patient data. This enables doctors to effectively monitor their patients. The developed application serves as a two-way communication bridge between patients and healthcare departments. Patients can effortlessly schedule appointments with their doctors for consultations and update their health status through the app. Simultaneously, doctors can conveniently issue prescriptions via the same application. We conducted a survey involving 120 participants, comprising 20 doctors and 100 patients. The results unequivocally demonstrate that the designed application has significantly improved healthcare management and fostered efficient communication between doctors and patients.